UTILITARISMO: DO ORTODOXISMO ECONÔMICO À POLÍTICA - SAUGO, DIEGO A.; BRUM, ARGEMIRO L.; SMOLSKI, FELIPE M. D. S.; WALDOW, HEITOR; ZINGLER, KARINE D.; FILHO, MAURICIO R. C. (Salão do Conhecimento, 2013)
Resumo